A Pilot Study on the Whole Exome Sequencing of Prostate Cancer in the Indian Phenotype Reveals Distinct Polymorphisms - Gupta, Ayam; Shukla, Nidhi; Nehra, Mamta; Gupta, Sonal; Malik, Babita; Mishra, Ashwani Kumar; Vijay, Maneesh; Batra, Jyotsna; Lohiya, Nirmal Kumar; Sharma, Devendra; Suravajhala, Prashanth (Frontiers in genetics, 2020)
Prostate cancer (PCa) is the third most common cancer among men in India, and no next-generation sequencing (NGS) studies have been attempted earlier. Recent advances in NGS have heralded the discovery of biomarkers from Caucasian/European and Chinese ancestry, but not much is known about the Indian phenotype/variant of PCa. In a pilot study using the whole exome sequencing of benign/PCa patients, we identified characteristic mutations specific to the Indian sub-population. We observed a large number of mutations in DNA repair genes, viz. helicases, TP53, and BRCA besides the variants of unknown significance with a possibly damaging rare variant (rs730881069/chr19:55154172C/TR136Q) in the TNNI3 gene that has been previously reported as a semi-conservative amino acid substitution. Our pilot study attempts to bring an understanding of PCa prognosis and recurrence for the Indian phenotype.Prostate cancer (PCa) is the third most common cancer among men in India, and no next-generation sequencing (NGS) studies have been attempted earlier. Recent advances in NGS have heralded the discovery of biomarkers from Caucasian/European and Chinese ancestry, but not much is known about the Indian phenotype/variant of PCa. In a pilot study using the whole exome sequencing of benign/PCa patients, we identified characteristic mutations specific to the Indian sub-population. We observed a large number of mutations in DNA repair genes, viz. helicases, TP53, and BRCA besides the variants of unknown significance with a possibly damaging rare variant (rs730881069/chr19:55154172C/TR136Q) in the TNNI3 gene that has been previously reported as a semi-conservative amino acid substitution. Our pilot study attempts to bring an understanding of PCa prognosis and recurrence for the Indian phenotype.